Merrylands - Central Mapping Authority of New South Wales (Bathurst, N.S.W. : Central Mapping Authority of N.S.W., 1983)
Orthophoto map with relief shown by contours and spot heights. Cadastral information overprinted in blue.
Includes legend and index to adjoining sheets.
Also available online
Keywords: Merrylands (N.S.W.) -- Maps; Photomaps